Analysis Of Dominant Factors Affecting Construction Service Providers On Tender Electronically In Malang Raya 2021 - Ayu Sabrina, Nabila; Wijatmiko, Indradi; Wisnumurti, Wisnumurti (Publisher Cv. Inara, 2023)
Provider process service construction participates in tenders electronics in Malang Raya; provider service construction will upload an offer or no for a project and make an offer that requires commitment source power. The influencing factors include the characteristics project, the ability company, the challenge operational project, the Economy, the environment, the market, and the government. The study aims to know the dominant factor influencing _ provider service construction bids on delicate electronics located in Malang Raya in 2021. Five hundred and fifty-nine respondents are provider service construction ever _ upload requirements nor only view tenders _ electronics at LPSE Malang Raya. Method research used _ is interviews and questionnaires — data analysis using Structure Equation Modeling (SEM) with SmartPLS (Partial Least Square) software. Modeling results bid Y = 0.123 X1 + 0.325 X2 + 0.196 X3 + 0.406 X4 Effect dominant leading provider service construction bid on Tender directly electronics at LPSE Malang Raya is a category of Economy, Environment, Market, and Government (X4) with Variable Replacement Value loss (X4.4). Influence dominant second that is category Enterprise Capability (X2) with variable Profitability (X2.3). Influence chief third category Challenge Operational Project (X3) with variable Availability another project (X3.4). And Influence dominant final category Characteristics Project (X1) with variable Tender Method (One File) (X1.8) Keywords: Tender, Construction Service Provider, Structural Equation Modeling (SEM), SmartPLS (Partial Least Square).